Rebellion of School-Age Youth in Poland - Iwona Murawska (Nicolaus Copernicus University in Toruń, 2020)
In the article below I explore the level of rebellion of modern youth, in the context of various ways of adapting to school and being a student. For research purposes I use an author's fivestage scale to measure student strategies. I developed the scale based on the model of adaptation by R. K. Merton. The study involves a group of 656 students aged 13-17 in Poland, and the analysis presented is part of a larger project on youth adaptation strategies. From all the answers provided, I select those relating to rebellion strategies. The results obtained show the average level of rebellion in the study group: means for rebellion statement range from 2.542 to 3.465 on a scale of 1 to 5. Many students feel a high level of satisfaction when they can point out mistakes to their teacher and want to speak their mind regarding school rules. However, generally this result shows that the statistical research subject has a rather neutral or positive attitude towards the goals pursued by the school. Findings indicate general approval within the tested population for entering into discussion with the teacher when the student feels the need or duty to defend his or her opinion but the mean for the statement referring to radical changes in the school indicates a relatively low need to completely change the existing school order